Causal pathways in preeclampsia: a Mendelian randomization study in European populations - Tan, Zilong; Ding, Mengdi; Shen, Jianwu; Huang, Yuxiao; Li, Junru; Sun, Aochuan; Hong, Jing; Yang, Yan; He, Sheng; Pei, Chao; Luo, Ran (Frontiers in Endocrinology, 2024)
Abstracts Purpose: Our study utilizes Mendelian Randomization (MR) to explore the causal relationships between a range of risk factors and preeclampsia, a major contributor to maternal and perinatal morbidity and mortality. Methods: Employing the Inverse Variance Weighting (IVW) approach, we conducted a comprehensive multi-exposure MR study analyzing genetic variants linked to 25 risk factors including metabolic disorders, circulating lipid levels, immune and inflammatory responses, lifestyle choices, and bone metabolism. We applied rigorous statistical techniques such as sensitivity analyses, Cochran’s Q test, MR Egger regression, funnel plots, and leave-one-out sensitivity analysis to address potential biases like pleiotropy and population stratification. Results: Our analysis included 267,242 individuals, focusing on European ancestries and involving 2,355 patients with preeclampsia. We identified strong genetic associations linking increased preeclampsia risk with factors such as hyperthyroidism, BMI, type 2 diabetes, and elevated serum uric acid levels. Conversely, no significant causal links were found with gestational diabetes, total cholesterol, sleep duration, and bone mineral density, suggesting areas for further investigation. A notable finding was the causal relationship between systemic lupus erythematosus and increased preeclampsia risk, highlighting the significant role of immune and inflammatory responses. Conclusion: This extensive MR study sheds light on the complex etiology of preeclampsia, underscoring the causal impact of specific metabolic, lipid, immune, lifestyle, and bone metabolism factors. Our findings advocate for a multidimensional approach to better understand and manage preeclampsia, paving the way for future research to develop targeted preventive and therapeutic strategies.